Adhesion improvement via surface functionalization of epoxy-resin base post by low temperature plasma - Waleepan Rakitikul (2018)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. The adhesion between dental materials could be improved by an increase of interfacial polarity. In this study, low temperature plasma was used to treat an epoxy-based post. The surface modifications after treatment were characterized by X-ray photoelectron spectroscopy (XPS) which showed the existence of N, O- containing groups in the epoxy-based post. Furthermore, functionalization positions were proposed by Quantum Mechanic (QM) calculation. It could confirm the position that such a functional group was formed at hydroxyl group and alpha-carbon with an energy level around 93-97 kcal/mol through hydrogen abstraction reaction. Both experiments and calculations show consistent results indicating polar group formation on the surface after plasma treatments.